PEMBAGIAN WARISAN DALAM HUKUM KELUARGA ISLAM: KONFLIK DAN SOLUSI DI PENGADILAN AGAMA - Neisty Pratiwi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2025)
This study aims to identify the factors that cause conflicts in the distribution of inheritance in the Religious Courts, analyze the settlement strategies applied based on Islamic Law, and examine the harmony between Islamic Family Law and the settlement solutions carried out. The research approach uses qualitative with case study design, data collection techniques including observation, interviews, and documentation. The data analysis uses the Miles and Huberman interactive model which includes the stages of data condensation, data presentation, and conclusion drawn. Data validity uses triangulation of sources and methods. The results of the study show that mediation is a means to resolve inheritance disputes, which is directed to achieve a peaceful consensus and ensure justice, especially in the fulfillment of women's rights. Religious Courts integrate the principles of Islamic Law by taking into account the values of customary law in order to produce a fair and socially acceptable verdict. However, in areas strongly influenced by customs, challenges remain. Therefore, legal education about inheritance rights based on sharia and the implementation of effective communication strategies in the mediation process are key to realizing a harmonious and fair settlement.